POLA DAN PROSES PENDIDIKAN TOLERANSI DALAM PEMBENTUKAN SIKAP TOLERANSI SISWA ANTAR UMAT BERAGAMA DI SMKN TUTUR - Siti Nur Asiyah; Asrul Anan (Journal Multicultural of Islamic Education, 2021)
The pattern and process of tolerance education referred to in the context of this study is the behavior of students who contain multicultural values ​​of tolerance. This study uses a qualitative method with a phenomenological approach. Data collection techniques are in-depth interviews, observation, and documentation. The subjects of the research were the principal, guardians of students and teachers who were Muslim, Christian and Catholic. The results of this study: First, the Education Pattern of Inter-religious Tolerance: a) Student involvement in democratic activities, b) Implementation of school rules, c) Cultivating an attitude of respect for friends who are worshiping, d) Cultivating human values, e) Cross-curricular extracurricular activities. Religion, f) Annual Ramadan program, g) Social service program, h) Halal bihalal activities every religious holiday, i) Student creativity program, j) Countering radicalism among teenagers, k) Holding youth seminars. Second, the teaching and learning process of tolerance education at SMKN Tutur, 1) Cognitive learning; Discussion activities between interfaith students, 2) Affective learning; halal bihalal every religious holiday, school anniversary, 3) Psychomotor learning; All students have the opportunity to be active in school organizations. Helping the smooth activities of non-Muslim students in celebrating religious holidays.